2018
DOI: 10.1177/2309499018816444
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of the reverse McLaughlin procedure for Hill–Sachs lesions in anterior shoulder instability

Abstract: Introduction: Engaging Hill-Sachs lesions in recurrent anterior shoulder dislocation have been managed with the remplissage procedure. Clinical and cadaveric studies have reported limitation of rotation after this procedure. We introduce the reverse McLaughlin procedure where the infraspinatus and the underlying capsule are detached and approximated into the Hill-Sachs defect with transosseous sutures. This is a preliminary report using this technique. Methods: Seventeen patients with recurrent anterior should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…Several studies have compared arthroscopic Bankart repair with remplissage to other procedures for anterior instability. Han et al [ 45 ] performed a retrospective study comparing the outcomes in patients who underwent arthroscopic Bankart repair with remplissage to those who underwent the reverse McLaughlin procedure for engaging HSLs and anterior shoulder instability at a single institution. At an average of 16.8 months of follow-up (range, 12–34 months), patients in the two groups had similar clinical outcome scores with no significant differences in preoperative or postoperative American Shoulder and Elbow Surgeons (ASES) score, Constant scores, 36-item short form survey (SF-36) physical component summary score, or SF-36 mental component summary score [ 45 ].…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have compared arthroscopic Bankart repair with remplissage to other procedures for anterior instability. Han et al [ 45 ] performed a retrospective study comparing the outcomes in patients who underwent arthroscopic Bankart repair with remplissage to those who underwent the reverse McLaughlin procedure for engaging HSLs and anterior shoulder instability at a single institution. At an average of 16.8 months of follow-up (range, 12–34 months), patients in the two groups had similar clinical outcome scores with no significant differences in preoperative or postoperative American Shoulder and Elbow Surgeons (ASES) score, Constant scores, 36-item short form survey (SF-36) physical component summary score, or SF-36 mental component summary score [ 45 ].…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Han et al [ 45 ] performed a retrospective study comparing the outcomes in patients who underwent arthroscopic Bankart repair with remplissage to those who underwent the reverse McLaughlin procedure for engaging HSLs and anterior shoulder instability at a single institution. At an average of 16.8 months of follow-up (range, 12–34 months), patients in the two groups had similar clinical outcome scores with no significant differences in preoperative or postoperative American Shoulder and Elbow Surgeons (ASES) score, Constant scores, 36-item short form survey (SF-36) physical component summary score, or SF-36 mental component summary score [ 45 ]. Another retrospective review by Hurley et al [ 46 ] showed no difference in outcomes after arthroscopic Bankart repair with remplissage compared to arthroscopic Latarjet for patients with anterior shoulder instability with a labral tear and engaging HSL.…”
Section: Clinical Outcomesmentioning
confidence: 99%